Pengaruh Halal Destination Image dan Tourism Experience terhadap Tourist Loyalty di Kota Padang - Respika Aprilia Putri; Rian Surenda (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is based on the identification of issues related to the halal destination image, tourism experience, and tourist loyalty. It is a type of quantitative research with a causal associative approach using survey methods. The data used are both primary and secondary. In this study, the sample includes 149 respondents selected using purposive sampling technique. Data collection was conducted through questionnaires using a Likert scale that had been tested for validity and reliability. The halal destination image variable achieved an average score of 88.2 with very good criteria. The average sample value is 0.461, the t-statistic value is 3.418, which is greater than 1.96, and the p-value is 0.001, which is less than 0.05. The tourism experience variable achieved an average score of 87.1 with very good criteria, the average sample value is 0.288, the t-statistic value is 2.107, which is greater than 1.96, and the p-value is 0.036, which is less than 0.05. The tourist loyalty variable has an average score of 86.7 with very good criteria, thus H1, H2, and H3 are accepted because they have a positive and significant impact on the halal destination image with tourist loyalty and tourism experience with tourist loyalty.